MEMOTRET KERAWANAN PANGAN DENGAN METODE HFIAS (Studi Kasus Di Salah Satu Desa Hutan Di Desa Lembu Kecamatan Bancak, Kabupaten Semarang) - Daru Purnomo (Cakrawala Jurnal Penelitian Sosial, 2015)
Food security is the nation's wealth and richness of farmers in the past, that now are decrease even disappear- replaced with production patterns and food-paced consumtive patterns, as a result of the introduction from the interests of neo-liberazation globalization farm that seems to be very "spoil/comforting", but behind that it was slowly "kill" cultural sectors, sovereignty even safety of a generation. This study aims to take a picture the condition of food insecurity that occurs in one forest villages, which is in the Lembu Village, Bancak District, and Semarang Region. The analysis used method of HFIAS (Household Food Insecurity Access Scale), whereas research process used survey method. The results showed that (1) The Village Community in general still have problems or lack of foods. Meanwhile, the enough foods amount is relatively few (and did not reach 30% of the total, which is only 22.2%). (2) Category enough food in this region can be easily slip over to the position of lack of foods rather than safe food, because in the dry season, food insecurity become a common phenomenon. (3) The strategy of survival were done by community in this village in times of food insecurity or paceklik[1] is by reducing types of daily foods or eating foods that is not desired. Keywords: Metode HFIAS, food security, food insecurity, Lembu village[1] Paceklik (Bahasa Jawa) yang berarti Musim kekurangan bahan makanan -KBBI